2018
DOI: 10.1002/ange.201712608
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Quenching in Self‐Assembled CsPbBr3 Quantum Dots on Few‐Layer Black Phosphorus Sheets

Abstract: An ordered self‐assembly of CsPbBr3 quantum dots (QDs) was generated on the surface of few‐layer black phosphorus (FLBP). Strong quenching of the QD fluorescence was observed, and analyzed by time‐resolved photoluminescence (TR‐PL) studies, DFT calculations, and photoconductivity measurements. Charge transfer by type I band alignment is suggested to be the cause of the observed effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…Additionally, the size of PHEMA- g -(PAA- b - c PS) was determined to be 35.1 nm in DMF and 22.8 nm in toluene according to the DLS measurements (Figure S7a-7b), further corroborating the collapsing of precursor-loaded polymer upon dropping into toluene. The NCs are highly crystalline with a d -spacing of 0.58 Å as revealed by high-resolution TEM (HRTEM) (Figure b), consistent with the previous report . The UV–vis absorption and photoluminescence (PL) spectra of c PS-capped CsPbBr 3 NCs are shown in Figure c, displaying a major absorption peak at 510 nm and a strong emission peak centered at 519 nm with a 17 nm full width at half-maximum (fwhm), coinciding well with the literature .…”
supporting
confidence: 89%
“…Additionally, the size of PHEMA- g -(PAA- b - c PS) was determined to be 35.1 nm in DMF and 22.8 nm in toluene according to the DLS measurements (Figure S7a-7b), further corroborating the collapsing of precursor-loaded polymer upon dropping into toluene. The NCs are highly crystalline with a d -spacing of 0.58 Å as revealed by high-resolution TEM (HRTEM) (Figure b), consistent with the previous report . The UV–vis absorption and photoluminescence (PL) spectra of c PS-capped CsPbBr 3 NCs are shown in Figure c, displaying a major absorption peak at 510 nm and a strong emission peak centered at 519 nm with a 17 nm full width at half-maximum (fwhm), coinciding well with the literature .…”
supporting
confidence: 89%
“…Besides the 2D–2D vdW heterojunction, BP can also be integrated with other low‐dimensional nanomaterials such as nanowires and quantum dots . Jeon et al reported BP nanosheet–ZnO nanowire 2D–1D heterojunctions for PN diodes with a high rectification ratio of 10 4 and kilohertz dynamic rectification as shown in Figure a–c .…”
Section: Bp‐based Optoelectronic and Photonic Applicationsmentioning
confidence: 99%
“…The synthesis procedure is illustrated in Figure d . Due to the efficient energy/charge transfer by type I band alignment at the BP–CsPbBr 3 interfaces, this hybrid structure shows great promise in optoelectronics . These works open new avenues for building novel devices with heterostructures based on materials with different/multiple dimensions.…”
Section: Bp‐based Optoelectronic and Photonic Applicationsmentioning
confidence: 99%
“…To overcome the instability issue of hybrid perovskites, recent efforts have been devoted to cesium lead halide perovskite (CsPbX 3 , X = halide ions) nanocrystals (NCs) due to their good stability, unique optical versatility, high luminescence quantum yields, and facile synthesis. However, in contrast to well-studied bulk CsPbX 3 , the phase transition behavior and photophysical properties of CsPbX 3 NCs have yet to be disserted fully. Until now, only a few studies of the phase transition have been conducted on such material systems. For instance, Bertolotti and coworkers investigated the structures of CsPbX 3 NCs and suggested that the local structure of these NCs always exhibits orthorhombic tilting of PbX 6 octahedra within locally ordered subdomains that are hinged through a two-/three-dimensional network of twin boundaries .…”
mentioning
confidence: 99%